2001
DOI: 10.1097/00005392-200109000-00028
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Efficacy of Sildenafil and Tachyphylaxis Effect

Abstract: Our data suggest that there is a possible tachyphylaxis effect with sildenafil. Of the patients who were followed for 2 years 20% had to increase the sildenafil dose to have the same effect and 17% discontinued use due to loss of efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
3

Year Published

2002
2002
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 14 publications
1
37
0
3
Order By: Relevance
“…El-Galley et al found that 43 (52%) out of 82 sildenafil users who had been followed-up for a period of 2 y were still using sildenafil at this time. 7 Their results seem comparable with the observations in this study, although it must be noted that 46% of the patients interviewed at baseline in the El-Galley study were lost to follow-up and results might therefore be biased. Studies on the efficacy of sildenafil have shown that the etiology of ED is a principal determinant of efficacy.…”
Section: Discussionsupporting
confidence: 85%
“…El-Galley et al found that 43 (52%) out of 82 sildenafil users who had been followed-up for a period of 2 y were still using sildenafil at this time. 7 Their results seem comparable with the observations in this study, although it must be noted that 46% of the patients interviewed at baseline in the El-Galley study were lost to follow-up and results might therefore be biased. Studies on the efficacy of sildenafil have shown that the etiology of ED is a principal determinant of efficacy.…”
Section: Discussionsupporting
confidence: 85%
“…20 Moreover, the tachyphylaxis effect from long-term use of sildenafil might need a dose escalation. 23,24 In the future, we might have to consider approval of the use of 100 mg sildenafil in Japan, too.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known, for several drug classes, that several doses are required to achieve an optimal response 6 and conversely there are drugs where repeated dosing can lead to pharmacological tolerance and diminution of effect. 7 The clinical trials data for apo SL detail the response to such sequential dosing under conditions of similar stimulus, in that the patients and their partners engaged in regular sexual attempts in a familiar environment. The reproducibility of effect with Uprima 1 has been documented 1 and in this analysis the efficacy enhancement with sequential dosing has been examined.…”
Section: Uprimamentioning
confidence: 99%